Artificial intelligence, big data, platform capitalism and public policy: an evolutionary perspective - Jacquinet, Marc (2019)
The present paper aims to discuss the change in political economy when considering the new context and complexity of social, environmental and economic issues today, and more recently all the debates around artificial intelligence, big data and platform capitalism. First, it is important that the reflection be situated in the new and latest phase of transformation of the capitalist system, either globally or locally. Second, the convergence between artificial intelligence, big data, computer science and platforms is not fortuitous and there is more than buzzwords, but new real economic processes emerging. Third, the evolutionary perspective adopted here is based on complexity theory and the recent developments in the study of innovation, technological change and institutions, from a rather heterodox view mixed with economic history. Fourth, the historical dimension of change and the need to adopt a long view of historical processes, namely because of uncertainty, ignorance and constraints on economic agents. Finally, the problem of framing political issues and measures is tackled and is related to the level of complexity of what is at stake with the digital transformation of capitalist economies and different types of democratic societies.